Occurrence of infectious diseases during the first two years and symptoms of asthma in six-year-old children (Research, Society and Development, 2022)
Objective: To observe possible association between the occurrence of infectious diseases during the first two years of life and the occurrence of asthma symptoms in six-year-old children. Methods: Cross-sectional study involving 956 six-year-old schoolchildren. Asthma symptoms were assessed through International Study of Asthma and Allergies in Childhood questionnaires. Socio-demographic data, mother-reported infectious diseases during the child's first two years of life, family history of asthma and breastfeeding were included. Multivariate analysis was performed with all significant variables and those with a p-value